Effect of ginger supplementation on the fecal microbiome in subjects with prior colorectal adenoma - Prakash, Ajay; Rubin, Nathan; Staley, Christopher; Onyeaghala, Guillaume; Wen, Ya-Feng; Shaukat, Aasma; Milne, Ginger; Straka, Robert J.; Church, Timothy R.; Prizment, Anna (Scientific reports, 2024)
Ginger has been associated with a decreased incidence of colorectal cancer (CRC) through reduction in inflammatory pathways and inhibition of tumor growth. Recent pre-clinical models have implicated changes in the gut microbiome as a possible mediator of the ginger effect on CRC. We hypothesized that, in adults previously diagnosed with a colorectal adenoma, ginger supplementation would alter the fecal microbiome in the direction consistent with its CRC-inhibitory effect. Sixty-eight adults were randomized to take either ginger or placebo daily for 6 weeks, with a 6-week washout and longitudinal stool collection throughout. We performed 16S rRNA sequencing and evaluated changes in overall microbial diversity and the relative abundances of pre-specified CRC-associated taxa using mixed-effects logistic regression. Ginger supplementation showed no significant effect on microbial community structure through alpha or beta diversity. Of 10 pre-specified CRC-associated taxa, there were significant decreases in the relative abundances of the genera Akkermansia (p < 0.001), Bacteroides (p = 0.018), and Ruminococcus (p = 0.013) after 6-week treatment with ginger compared to placebo. Ginger supplementation led to decreased abundances of Akkermansia and Bacteroides , which suggests that ginger may have an inhibitory effect on CRC-associated taxa. Overall, ginger supplementation appears to have a limited effect on gut microbiome in patients with colorectal adenomas.